Evaluation of ERDT's R&D Performance in the Semiconductor and Electronics Sector - Pariñas, May-Rose Bagunu (Technology Management Center, 2014)
The Semiconductor and electronics industries have been facing internal challenges in the past decade due to fluctuating currency rates and high energy costs top it all, the competition threat amongst our neighboring countries is intense as ever, with the generous incentives made available by their respective governments. In April 2007, the Engineering Research and Development for Technology (ERDT) Program was approved by former President Arroyo with a P3.5 billion funding for three years. The ERDT is a consortium of seven-member universities in the country that offers mature master's and doctoral degrees in various engineering fields. The consortium constitutes De La Salle University, Mapua Institute of Technology, Ateneo de Manila University, Mindanao State University Iligan, University of San Carlos, Central Luzon State University, and the University of the Philippines Diliman. Reviewing the performance of ERDT based on four criteria, namely, relevance, effectiveness, impact and sustainability, the program was found to have directly and indirectly accomplished the following outputs : (1) implemented a "pilot engineering research program" which might not be high-impact at this point but have initiated a good foundation for the universities; (2) produced initial batch of graduates with Master's and PhD degrees to promote electronics engineering course; (3) upgraded the qualifications of practicing engineers; (4) upgraded the engineering program by providing the funding resources and infrastructure to produce quality R&D projects; and make engineering graduate education accessible to local scholars; and (5) developed a culture of research and development (R&D) among students and faculty. Implementation of the ERDT however, has to be fully documented, consolidated and made accessible to facilitate monitoring, evaluation. Evaluation of project performance based on ERDT experience could be further improved based on the several recommendations provided in this paper